Dielectric screening of excitons in monolayer graphene. Issue 43 (15th October 2015) - Yadav, Premlata; Srivastava, Pawan Kumar; Ghosh, Subhasis
Abstract : Dielectric screening of excitons in monolayer graphene has been evidenced by a shift in excitonic peaks in various dielectric environments. The scaling relationship E b ∝ ε −1.2 has also been established. Abstract : Excitonic transitions in graphene monolayers embedded in different dielectric environments have been investigated using combined absorption and transmission spectroscopy techniques. To vary the dielectric environment, graphene monolayer has been exfoliated in liquid medium. It has been shown that exciton binding energy decreases with increase in the dielectric constant of exfoliating solvents due to the screening of electron–electron and electron–hole interactions in graphene. The typical line shape of the excitonic peak in the absorption spectra is explained by the Fano resonance between the excitonic state and band continuum. Further it has been shown that, there exists a scaling relationship between the dielectric constant of the liquid and the exciton binding energy.